Gandhian Thoughts for sustainable Environment: Essential Requirement for the Bright Future of Tourism in India - Arunesh Parashar; Ipsit Pratap Singh; Prachi Agarwal; Aditya Pratap Singh (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
Indian tourism industry has undoubted bright future. The rate of tourist’s arrival is rising day by day. But the biggest question is ‘do we get this growth on the cost of our ecology and environment’ or we can have sustainable growth in the field of tourism. Superficially, it looks that we have taken the idea of sustainable growth and development from western nations. But we Indians have this thought since ancient India. Moreover nine decades back an Indian seer, saint and philosopher came back to India to remind these ancient ideas in modern context. He gave the message of ecological wisdom, participatory democracy, Non – violence not just through his tongue but also by his actions. In the present context Gandhian philosophies become more relevant especially for the conservation of our environment. Generally tourist consider the exploitation of environment as their birth right without thinking about the future generations. Mahatma Gandhi gave the applicable concepts on sustainable environment which are actually very important for the bright future of Indian tourism.  Though in tourism industry there are many existing concepts on sustainability. But still we need to apply the Gandhian principles for the betterment of Indian Tourism. Some famous tourist destinations applied these principles and the results are favourable. In the present research paper author duo attempted to bring some new dimensions on the relevance of Gandhian thoughts for the bright future of Indian tourism.